Application of Natural Dyeing Technology through Eco-print for Eco-Friendly Textile Production in the Bantul Region - Adiyanto, Okka; Utami, Endah; Bariyah, Choirul; Faishal, Muhammad; Mohamad, Effendi; Maksum, Ali (Universitas Ahmad Dahlan, 2025)
Background: Bantul Regency in Indonesia has strong potential to develop a sustainable creative economy through local crafts. However, many MSMEs still use synthetic dyes that harm the environment. This program aimed to introduce Eco-print, a natural dyeing technique using local leaves and flowers. Contribution: The initiative raised awareness about sustainable production, built technical skills, and encouraged home-based creative enterprises. It supported the community in adopting local resource-based innovations while promoting environmental responsibility and cultural expression. Method: This program using a Community Development approach, with six stages: needs assessment, collaborative planning, Eco-print training, mentoring, and evaluation. Training activities included plant identification, motif design, and natural dye fixation, conducted with the KSS Berkah Bersama community. Results: Post-training assessments showed a significant improvement in knowledge and skill, with test scores increasing from 40–50 to 80–90. Participants produced eco-friendly tote bags and expressed interest in continuing independent production and marketing efforts. Conclusion: The program effectively built sustainable textile skills, empowered community members through practical innovation, and supported inclusive local economic development rooted in environmental values and cultural identity.